Antioxidant activity of pithecellobium bubalinum in several preparation of seed intake / Norazmunira Ibrahim - Ibrahim, Norazmunira (Faculty of Applied Sciences, 2017)
Pithecellobium bubalinum or better known as 'Kerdas' among Malaysians is a type of 'ulam' that is used in traditional medicine to treat various kind of diseases such as reduced cardiovascular diseases and certain cancers. This study aims to increase the awareness of folks about antioxidant potential in P. bubalinum, to determine the antioxidant properties in ethanol extract and finally to suggest the best way of consuming P. bubalinum seeds in a way that the most effective in terms of antioxidant content. DPPH radical-scavenging activity of P. bubalinum was evaluated by using the formula to obtain the percentage of DPPH control. While total phenolic was determined by the Folin-Ciocalteu method and calibration curve with gallic acid as standard solution was plotted. Results showed roasted seed extract at concentration 50 μg/ml had the least DPPH radical scavenging activity of 58.74% whereas raw seed extract at concentration 200 μg/ml had the highest activity of 96.84%. As for the TPC, the result showed that phenolic content in ethanol was 10.10 GAE/ml in raw seed eating, 6.53 GAE/ml for roasted seeds by direct flame and 8.97 GAE/ml for curing seeds in soil. Hence, raw seed extract are the best method compared to roasted and curing in soil seeds extract based from the result in the DPPH assay and TPC. There are antioxidants activities of P. bubalinum in ethanol extract.